Case report: Usefulness of angioscopy in determining antiplatelet drug reduction after carotid artery stenting - Fukutome, Kenji; Shiba, Mikio; Aketa, Shuta; Mitsui, Takaaki; Shiraishi, Yuki; Hayami, Hiromichi; Murakami, Yasutaka; Matsuoka, Ryuta; Tei, Rinsei; Shin, Yasushi; Motoyama, Yasushi (Frontiers in Neurology, 2023)
We report a case in which the neointima was confirmed by angioscopy and the antiplatelet drug was reduced two months after carotid artery stenting (CAS). A patient in their 80s was scheduled to undergo resection for renal cancer, but he also had right cervical internal carotid artery stenosis. Because it was a risk for general anaesthesia, CAS was performed after starting dual antiplatelet therapy at first. Urologically, early reduction of antiplatelet drugs was necessary for the nephrectomy. Although no obvious neointima could be identified on ultrasound two months after CAS, thin neointima was observed by angioscopy. Based on the above results, we reduced the antiplatelet drug, and then nephrectomy was performed. Ultimately, no cerebral infarction occurred in the perioperative period and postoperatively. Angioscopy allows visual confirmation of the thin neointima. If sufficient neointima can be confirmed, antiplatelet drug reduction can be performed more safely and reliably.